Inroads : paths in ancient and modern western philosophy - Miles, Murray Lewis, 1946- (Toronto studies in philosophy., 2003)
In each of its five main parts - in turn, focusing on Socrates, Plato, Descartes, Hume, and Sartre - Inroads discusses, from a philosophical rather than a religious or scientific perspective, those questions that make up the common inheritance of academic philosophy and ethico-religious thought.